Porous battery diaphragm and preparation method thereof

By using sandwich structure and phosphoric acid modification treatment of polyvinylidene fluoride film and silica/zirconia fiber membrane in the battery separator, the problem of poor mechanical properties of the battery separator is solved, and high ion mobility and high temperature self-amounting performance are achieved , extends the service life of the battery separator and improves the overall performance of the battery.

CN119297529APending Publication Date: 2025-01-10YANGQUAN CITY REGIONAL INNOVATION PROMOTION CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411535063.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The mechanical properties of existing battery separators are poor, making it difficult to meet the requirements of high ion mobility and high temperature autism performance of lithium-ion batteries.

Method used

Multi-layer battery separator with sandwich structure is formed by polyvinylidene fluoride film and silica/zirconia fiber film, and modified by phosphoric acid to improve the mechanical strength of the fiber membrane and electrolyte affinity. sex.

Benefits of technology

It significantly improves the mechanical strength and electrolyte affinity of the battery separator, extends the service life of the battery separator, and enhances the safety and performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of battery diaphragms, and particularly discloses a porous battery diaphragm and a preparation method thereof. The porous battery diaphragm comprises a polyvinylidene fluoride film, a composite fiber film and a polyvinylidene fluoride film which are arranged in sequence, and the composite fiber film is a silicon dioxide / zirconium oxide fiber film; the preparation method comprises the following steps: S1, preparing the composite fiber membrane; s2, preparing a polyvinylidene fluoride solution; and S3, preparing the porous battery diaphragm. The porous battery diaphragm disclosed by the invention can be used in a battery, has extremely high electrolyte affinity, dimensional stability, thermal stability, fire resistance and light weight, and has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and more specifically, to a porous battery separator and a preparation method thereof. Background Art

[0002] Battery separator refers to the polymer separator between the positive and negative electrodes of lithium-ion batteries. It is a key component of lithium-ion batteries. It plays a role in directly separating the positive and negative electrodes in structure and preventing battery short circuit, which has a direct impact on battery safety and cost. The main function is to isolate the positive and negative electrodes and prevent the electrons in the battery from passing freely, allowing the lithium ions in the electrolyte to pass freely between the positive and negative electrodes. In addition to the performance requirements of ordinary separator materials, battery separators must also meet requirements such as high ion migration number, excellent chemical and electrochemical stability, good mechanical properties, and high liquid retention rate. When overcharged or the temperature rises, the separator also has high-temperature self-closing properties to prevent current conduction and explosion.

[0003] At present, the most widely used polyolefin diaphragms are the commonly used PP and PE diaphragms. Due to the physical property limitations of the raw materials, the lyophilicity and high temperature resistance of the diaphragms are limited. There are three ways to improve: 1. Add or compound materials with lyophilicity and high temperature resistance to the general diaphragm to improve the performance. The commonly used processes currently include coating, dipping, spraying, and compounding. For example, power batteries are coated with high-temperature stable coatings such as aluminum oxide and zirconium oxide on the diaphragm. 2. Replace with some materials with excellent comprehensive performance, such as polyvinylidene fluoride (PVDF), polyimide, aramid and cellulose. 3. Regulation of the diaphragm structure morphology. Smaller pore size, higher porosity and internally interconnected open pore structure are conducive to improving the ion mobility of lithium batteries. Non-woven weaving technology, including melt spinning, solution spinning, electrospinning and other processes, has the characteristics of high porosity, small nano size, and relatively uniform thickness. Through process optimization, it can meet the requirements of lithium-ion battery diaphragms. Electrospinning also has its shortcomings. Compared with traditional membranes, electrospinning often has poor mechanical properties, low production efficiency and high cost.

[0004] However, the battery separators modified by the current conventional methods still have the problem of poor mechanical properties, so further improvements to the battery separators are needed. Summary of the invention

[0005] In order to improve the defect of poor mechanical properties of battery separators, the present application provides a porous battery separator and a preparation method thereof.

[0006] The present application provides a porous battery separator, which adopts the following technical solution: In a first aspect, the present application provides a porous battery separator, comprising a polyvinylidene fluoride film, a composite fiber membrane and a polyvinylidene fluoride film arranged in sequence, wherein the composite fiber membrane is a silica / zirconia fiber membrane.

[0007] By adopting the above technical solution, polyvinylidene fluoride has excellent mechanical properties, thermal stability and chemical stability and is easy to form a film. The silica / zirconia fiber membrane has excellent tensile strength, flexibility and high-temperature thermal insulation effect. Silica and zirconium oxide can promote the formation of a four-directional structure in the fiber membrane, inhibit the formation of a monoclinic phase, and enable the fiber membrane to obtain excellent mechanical strength. Furthermore, the multilayer battery separator formed by the sandwich structure of polyvinylidene fluoride film and composite fiber membrane can obtain excellent mechanical strength, and the introduction of zirconium oxide in the composite fiber membrane can effectively improve the electrolyte affinity of the battery separator, which is beneficial to the application effect of the battery separator in the battery.

[0008] Optionally, the composite fiber membrane is prepared as follows: polyvinyl pyrrolidone is added to HNO3, stirred to dissolve, then N'N-dimethylformamide and vinyltrimethoxysilane are added in sequence, stirred to obtain solution A, zirconium n-butoxide and acetic acid are mixed to obtain solution B, a certain amount of solution B is added to solution A, stirred to obtain a polyzirconium siloxane spinning solution, and electrospinning is performed to prepare a precursor fiber membrane, the precursor fiber membrane is dried at 80°C for 6 h, placed in a muffle furnace, heated to 1000°C at a rate of 5°C / min in an air atmosphere, and kept warm for 1 h to obtain a composite fiber membrane.

[0009] Optionally, the polyvinylidene fluoride film comprises polyvinylidene fluoride and silicon dioxide, and the silicon dioxide is amino silicon dioxide modified by a silane coupling agent.

[0010] By adopting the above technical scheme, preferably adding silica particles to the polyvinylidene fluoride film and performing amino modification on the nano-silica, the dispersion uniformity of the nano-silica in the polyvinylidene fluoride film can be effectively improved, so that the nano-silica can uniformly improve the mechanical strength of the polyvinylidene fluoride. Moreover, since both the polyvinylidene fluoride film and the composite fiber membrane contain nano-silica, the mechanical strength of the battery separator can be effectively improved.

[0011] Optionally, the silica is phosphoric acid-modified silica.

[0012] By adopting the above technical scheme, preferably using phosphoric acid to modify the silica, the phosphoric acid-modified silica can introduce phosphoric acid groups into the polyvinylidene fluoride film, and the phosphoric acid groups can chelate with zirconium, effectively improving the bonding effect between the polyvinylidene fluoride film and the composite fiber membrane, extending the service life of the battery separator, and improving the mechanical strength of the battery film.

[0013] Optionally, the phosphorylated modified silica is prepared as follows: dispersing silica in water, adding phosphoric acid, stirring, volatilizing in a water bath, grinding, roasting, washing, and drying to obtain phosphorylated modified silica.

[0014] Optionally, the polyvinylidene fluoride film further includes cellulose acetate, and the mass ratio of the polyvinylidene fluoride to cellulose acetate is 8-9:1-2.

[0015] By adopting the above technical solution, it is preferred to add cellulose acetate to the polyvinylidene fluoride film. The introduction of cellulose acetate can inhibit the crystallinity of polyvinylidene fluoride, increase the porosity of the polyvinylidene fluoride film, and improve the affinity between the polyvinylidene fluoride film and the electrolyte. The amount of cellulose acetate added is optimized, and the appropriate amount of addition can increase the porosity and mechanical strength of the polyvinylidene fluoride surface. Too much cellulose acetate addition is more likely to cause excessive damage to the PVDF crystal region and the film has a higher density, which reduces the mechanical strength of polyvinylidene fluoride and the electrolyte affinity.

[0016] Optionally, the mass ratio of polyvinylidene fluoride, cellulose acetate and nano-silicon dioxide in the polyvinylidene fluoride film is 8-9:1-2:0.9.

[0017] By adopting the above technical solution, the addition amount of nano-silicon dioxide is further optimized. The appropriate addition of nano-silicon dioxide is beneficial to the formation of pores in the polyvinylidene fluoride film, and can be evenly dispersed in the polyvinylidene fluoride film and play a supporting role, thereby improving the mechanical strength of the polyvinylidene fluoride film and the electrolyte affinity.

[0018] Optionally, PET fibers are added to the polyvinylidene fluoride film.

[0019] By adopting the above technical solution, it is preferred to add PET fiber to the polyvinylidene fluoride film. The PET fiber has a better bonding effect with the polyvinylidene fluoride film. The PET fiber can stably act as a supporting material in the polyvinylidene fluoride film, forming a stable staggered structure in the polyvinylidene fluoride film, and stably improving the mechanical strength of the film.

[0020] Optionally, the PET fiber is PET fiber modified with sodium alginate.

[0021] By adopting the above technical solution, preferably using sodium alginate to modify the PET fiber, sodium alginate can improve the bonding effect between the PET fiber and polyvinylidene fluoride, and sodium alginate can also co-construct a cross-linked network in the polyvinylidene fluoride, further improving the mechanical strength of the polyvinylidene fluoride film. At the same time, since sodium alginate has better viscosity, it is beneficial to improve the bonding strength between the polyvinylidene fluoride film and the composite fiber film, so that the battery separator can maintain a whole, and extend the service life of the battery separator.

[0022] In a second aspect, the present application provides a method for preparing a porous battery separator, using the following technical solution: A method for preparing a porous battery separator comprises the following steps: S1. Preparation of composite fiber membrane: lay the composite fiber membrane flat on a glass plate; S2, polyvinylidene fluoride solution preparation: dissolving polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stirring to obtain a mixed solution, adding nano-scale silicon dioxide powder, stirring to obtain a uniform solution, and obtaining a polyvinylidene fluoride solution; S3. Preparation of porous battery separator: Use a scraper to uniformly coat the casting liquid on both sides of the fiber membrane at a uniform speed. The coating amount of the casting liquid is 0.1 ml / cm 2 The ceramic fiber coated with the casting solution is dried at 80°C to evaporate the NMP solvent, and then dried to obtain a porous battery separator.

[0023] In summary, this application has the following beneficial effects: 1. Since the multilayer battery separator formed by a sandwich structure of polyvinylidene fluoride film and composite fiber membrane in the present application can obtain excellent mechanical strength, and since the introduction of zirconium oxide in the composite fiber membrane can effectively improve the electrolyte affinity of the battery separator, it is beneficial to the application effect of the battery separator in the battery.

[0024] 2. In the present application, phosphoric acid is preferably used to modify silica. Phosphoric acid-modified silica can introduce phosphoric acid groups into the polyvinylidene fluoride film. The phosphoric acid groups can chelate with zirconium, effectively improving the bonding effect between the polyvinylidene fluoride film and the composite fiber membrane, extending the service life of the battery separator, and improving the mechanical strength of the battery film.

[0025] 3. The present application preferably uses sodium alginate to modify the PET fiber. Sodium alginate can improve the bonding effect between the PET fiber and polyvinylidene fluoride, and sodium alginate can also co-construct a cross-linked network in the polyvinylidene fluoride to further improve the mechanical strength of the polyvinylidene fluoride film. At the same time, since sodium alginate has better viscosity, it is beneficial to improve the bonding strength between the polyvinylidene fluoride film and the composite fiber film, so that the battery separator can maintain a whole and extend the service life of the battery separator. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Preparation Example Preparation Example of Phosphated Silica Preparation Example 1 Weigh 0.4g of nano-silica in a 50mL beaker, add 10mL of ultrapure water, take 18.2µL of phosphoric acid (theoretical P loading is 2%) and add it to the above suspension. After stirring at room temperature for 10 minutes, place the beaker containing the suspension in an 80℃ water bath and stir to evaporate and remove water. The obtained solid is ground and calcined in a 400℃ muffle furnace at a heating rate of 2℃ / min for 25 minutes, then centrifuged and washed with ultrapure water 3 times, and the obtained solid is dried at 80℃, cooled to room temperature, and ground into powder to obtain phosphorylated silica.

[0028] Preparation Example of Aminated Silica Preparation Example 2 0.4 g of nano-silica was weighed into a 50 mL beaker, 10 mL of ultrapure water was added thereto to prepare a suspension, KH550 was added to the suspension, the mixture was stirred and mixed, filtered, and dried to obtain amino-silica.

[0029] Modified PET fiber preparation example Preparation Example 3 Sodium alginate is mixed with water to obtain a mixed solution with a mass fraction of 2%; chitosan is mixed with 0.1 mol / L hydrochloric acid solution to obtain an acid solution with a mass fraction of 2%; PET fiber is first immersed in the acid solution, then immersed in the mixed solution, washed, and dried to obtain modified PET fiber.

[0030] Example

[0031] Example 1 On the one hand, the present application provides a porous battery separator, comprising a polyvinylidene fluoride film, a composite fiber membrane and a polyvinylidene fluoride film arranged in sequence, wherein the composite fiber membrane is a silica / zirconia fiber membrane.

[0032] In another aspect, the present application provides a method for preparing a porous battery separator, comprising the following steps: S1. Preparation of composite fiber membrane: The composite fiber membrane is prepared as follows: first, polyvinyl pyrrolidone is added to 1 mol / L HNO3, and stirred at 400 r / min for 1 h to fully dissolve the polyvinyl pyrrolidone. Then, N'N-dimethylformamide and vinyl trimethoxysilane are added in sequence, and solution A is obtained after stirring for 6 h. Zirconium n-butoxide and acetic acid are mixed evenly to obtain solution B. Solution B is added to solution A, and stirred for 1 h to obtain a polyzirconium siloxane spinning solution (a precursor spinning solution with a vinyl trimethoxysilane / zirconium n-butoxide molar ratio of 1:2). The prepared polyzirconium siloxane spinning solution is used for electrospinning to prepare a precursor fiber membrane, and the spinning voltage is set to 15 kV, the spinning distance is 15 cm, and the liquid push rate is set to 0.9 mL / min. The precursor fiber membrane was dried at 80°C for 6 hours and then placed in a muffle furnace. The temperature was raised to 1000°C at a rate of 5°C / min in an air atmosphere. After being kept at this temperature for 1 hour, a SiO2 / ZrO2 nanofiber membrane was obtained. The composite fiber membrane was laid flat on a glass plate. S2, polyvinylidene fluoride solution preparation: polyvinylidene fluoride-hexafluoropropylene powder is dissolved in 1-methyl-2-pyrrolidone solution, stirred to obtain a mixed solution with a mass fraction of 6%, and 0.2% of the amino-modified nano-silica powder prepared in Preparation Example 2 is added, stirred to obtain a uniform solution, and a polyvinylidene fluoride solution is obtained; S3. Preparation of porous battery separator: Use a scraper to uniformly coat the casting liquid on both sides of the fiber membrane at a uniform speed. The coating amount of the casting liquid is 0.1 ml / cm 2 The ceramic fiber coated with the casting solution is dried at 80°C to evaporate the NMP solvent, and then dried to obtain a porous battery separator.

[0033] Example 2 On the one hand, the present application provides a porous battery separator, comprising a polyvinylidene fluoride film, a composite fiber membrane and a polyvinylidene fluoride film arranged in sequence, wherein the composite fiber membrane is a silica / zirconia fiber membrane.

[0034] In another aspect, the present application provides a method for preparing a porous battery separator, comprising the following steps: S1. Preparation of composite fiber membrane: The composite fiber membrane is prepared as follows: first, polyvinyl pyrrolidone is added to 1 mol / L HNO3, and stirred at 400 r / min for 1 h to fully dissolve the polyvinyl pyrrolidone. Then, N'N-dimethylformamide and vinyl trimethoxysilane are added in sequence, and solution A is obtained after stirring for 6 h. Zirconium n-butoxide and acetic acid are mixed evenly to obtain solution B. Solution B is added to solution A, and stirred for 1 h to obtain a polyzirconium siloxane spinning solution (a precursor spinning solution with a molar ratio of vinyl trimethoxysilane / zirconium n-butoxide of 1:1). The prepared polyzirconium siloxane spinning solution is used for electrospinning to prepare a precursor fiber membrane, and the spinning voltage is set to 15 kV, the spinning distance is 15 cm, and the liquid push rate is set to 0.9 mL / min. The precursor fiber membrane was dried at 80°C for 6 hours and then placed in a muffle furnace. The temperature was raised to 1000°C at a rate of 5°C / min in an air atmosphere. After being kept at this temperature for 1 hour, a SiO2 / ZrO2 nanofiber membrane was obtained. The composite fiber membrane was laid flat on a glass plate. S2, polyvinylidene fluoride solution preparation: polyvinylidene fluoride-hexafluoropropylene powder is dissolved in 1-methyl-2-pyrrolidone solution, stirred to obtain a mixed solution with a mass fraction of 6%, and 0.2% of the amino-modified nano-silica powder prepared in Preparation Example 2 is added, stirred to obtain a uniform solution, and a polyvinylidene fluoride solution is obtained; S3. Preparation of porous battery separator: Use a scraper to uniformly coat the casting liquid on both sides of the fiber membrane at a uniform speed. The coating amount of the casting liquid is 0.1 ml / cm 2 The ceramic fiber coated with the casting solution is dried at 80°C to evaporate the NMP solvent, and then dried to obtain a porous battery separator.

[0035] Example 3 On the one hand, the present application provides a porous battery separator, comprising a polyvinylidene fluoride film, a composite fiber membrane and a polyvinylidene fluoride film arranged in sequence, wherein the composite fiber membrane is a silica / zirconia fiber membrane.

[0036] In another aspect, the present application provides a method for preparing a porous battery separator, comprising the following steps: S1. Preparation of composite fiber membrane: The composite fiber membrane is prepared as follows: first, polyvinyl pyrrolidone is added to 1 mol / L HNO3, and stirred at 400 r / min for 1 h to fully dissolve the polyvinyl pyrrolidone. Then, N'N-dimethylformamide and vinyl trimethoxysilane are added in sequence, and solution A is obtained after stirring for 6 h. Zirconium n-butoxide and acetic acid are mixed evenly to obtain solution B. Solution B is added to solution A, and stirred for 1 h to obtain a polyzirconium siloxane spinning solution (a precursor spinning solution with a vinyl trimethoxysilane / zirconium n-butoxide molar ratio of 2:1). The prepared polyzirconium siloxane spinning solution is used for electrospinning to prepare a precursor fiber membrane, and the spinning voltage is set to 15 kV, the spinning distance is 15 cm, and the liquid push rate is set to 0.9 mL / min. The precursor fiber membrane was dried at 80°C for 6 hours and then placed in a muffle furnace. The temperature was raised to 1000°C at a rate of 5°C / min in an air atmosphere. After being kept at this temperature for 1 hour, a SiO2 / ZrO2 nanofiber membrane was obtained. The composite fiber membrane was laid flat on a glass plate. S2, polyvinylidene fluoride solution preparation: polyvinylidene fluoride-hexafluoropropylene powder is dissolved in 1-methyl-2-pyrrolidone solution, stirred to obtain a mixed solution with a mass fraction of 6%, and 0.2% of the amino-modified nano-silica powder prepared in Preparation Example 2 is added, stirred to obtain a uniform solution, and a polyvinylidene fluoride solution is obtained; S3. Preparation of porous battery separator: Use a scraper to uniformly coat the casting liquid on both sides of the fiber membrane at a uniform speed. The coating amount of the casting liquid is 0.1 ml / cm 2 The ceramic fiber coated with the casting solution is dried at 80°C to evaporate the NMP solvent, and then dried to obtain a porous battery separator.

[0037] Example 4 The difference from Example 1 is: S2. Preparation of polyvinylidene fluoride solution: dissolve polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stir to obtain a mixed solution with a mass fraction of 6%, add 0.2% of the phosphorylated nano-silica powder prepared in Preparation Example 1, stir to obtain a uniform solution, and obtain a polyvinylidene fluoride solution; prepare a porous battery separator.

[0038] Example 5 The difference from Example 1 is: S2. Preparation of polyvinylidene fluoride solution: dissolve polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stir to obtain a mixed solution with a mass fraction of 6%, add 0.1% of the amino-modified nano-silica powder prepared in Preparation Example 2, 0.1% of the phosphorylated nano-silica powder prepared in Preparation Example 1 and cellulose acetate, the specific mass ratio of polyvinylidene fluoride to cellulose acetate is 8:2, stir to obtain a uniform solution, and obtain a polyvinylidene fluoride solution; prepare a porous battery separator.

[0039] Example 6 The difference from Example 1 is: S2. Preparation of polyvinylidene fluoride solution: dissolve polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stir to obtain a mixed solution with a mass fraction of 6%, add 0.1% of the amino-modified nano-silica powder prepared in Preparation Example 2, 0.1% of the phosphorylated nano-silica powder prepared in Preparation Example 1 and cellulose acetate, the specific mass ratio of polyvinylidene fluoride to cellulose acetate is 9:1, stir to obtain a uniform solution, and obtain a polyvinylidene fluoride solution; prepare a porous battery separator.

[0040] Example 7 The difference from Example 1 is: S2. Preparation of polyvinylidene fluoride solution: dissolve polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stir to obtain a mixed solution with a mass fraction of 6%, add the amino-silica powder prepared in Preparation Example 2, the phosphated nano-silica powder prepared in Preparation Example 1 and cellulose acetate, specifically, the mass ratio of polyvinylidene fluoride, cellulose acetate and nano-silica (nano-silica includes the amino-silica prepared in Preparation Example 2 and the phosphated silica prepared in Preparation Example 1) is 9:1:0.9, stir to obtain a uniform solution, and obtain a polyvinylidene fluoride solution; prepare a porous battery separator.

[0041] Example 8 The difference from Example 1 is: S2. Preparation of polyvinylidene fluoride solution: dissolve polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stir to obtain a mixed solution with a mass fraction of 6%, add the amino-silica powder prepared in Preparation Example 2, the phosphated nano-silica powder prepared in Preparation Example 1, cellulose acetate and PET fiber, specifically, the mass ratio of polyvinylidene fluoride, cellulose acetate, nano-silica (nano-silica includes the amino-silica prepared in Preparation Example 2 and the phosphated silica prepared in Preparation Example 1) and PET fiber is 9:1:0.9:0.2, stir to obtain a uniform solution, and obtain a polyvinylidene fluoride solution; prepare a porous battery separator.

[0042] Example 9 The difference from Example 1 is: S2. Preparation of polyvinylidene fluoride solution: dissolve polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stir to obtain a mixed solution with a mass fraction of 6%, add the amino nano-silica powder prepared in Preparation Example 2, the phosphorylated nano-silica powder prepared in Preparation Example 1, cellulose acetate and the modified PET fiber prepared in Preparation Example 3, specifically, the mass ratio of polyvinylidene fluoride, cellulose acetate, nano-silica (nano-silica includes the amino nano-silica prepared in Preparation Example 2 and the phosphorylated silica prepared in Preparation Example 1) and PET fiber is 9:1:0.9:0.2, stir to obtain a uniform solution, and obtain a polyvinylidene fluoride solution; prepare a porous battery separator.

[0043] Comparative Example Comparative Example 1 The difference between this comparative example and Example 3 is that the battery separator in this comparative example only includes the composite fiber membrane.

[0044] Performance testing (1) Tensile strength test: The tensile strength of the battery separator was tested according to GB / T1040.3-2006.

[0045] (2) Porosity and liquid absorption measurement: Weigh the mass of the membrane before and after treatment respectively, and calculate using the formula.

[0046] Among them, the solvent used in the porosity test is n-butanol, and the calculation method is: porosity (%) = (Wt-Wo) / ρV×100 (ρ-density of n-butanol, V-sample volume); the solution used in the liquid absorption test is electrolyte, and the calculation method is: liquid absorption (%) = (Wb-Wa) / Wa×100 (Wa-mass of sample before liquid absorption, Wb-mass of sample after liquid absorption).

[0047] (3) Scratch resistance test: The film was subjected to a tensile peeling performance test according to GB / T1040.3-2006, with a tensile rate of 10 mm / min.

[0048] Table 1 Performance test

[0049] The peel strength between the polyvinylidene fluoride film and the composite fiber membrane in Example 3 is 212 N / m, and the peel strength between the polyvinylidene fluoride film and the composite fiber membrane in Example 9 is 238 N / m.

[0050] Combining the performance test comparison in Table 1, we can find that: 1. By comparing Examples 1-3 with Comparative Example 1, it can be found that the tensile strength, porosity and liquid absorption of the battery separators prepared in Examples 1-3 are improved, which means that the multilayer battery separators formed by a sandwich structure of polyvinylidene fluoride film and a composite fiber membrane in the present application can obtain excellent mechanical strength, and the introduction of zirconium oxide in the composite fiber membrane can effectively improve the electrolyte affinity of the battery separator, which is beneficial to the application effect of the battery separator in the battery.

[0051] 2. By comparing Example 4 with Example 1, it can be found that the tensile strength, porosity and liquid absorption of the battery separator prepared in Example 4 are all improved, which means that the phosphoric acid-modified silica in the present application can introduce phosphoric acid groups into the polyvinylidene fluoride film, and the phosphoric acid groups can chelate with zirconium, effectively improving the bonding effect between the polyvinylidene fluoride film and the composite fiber membrane, extending the service life of the battery separator, and improving the mechanical strength of the battery film.

[0052] 3. By comparing Examples 5-6 with Example 1, it can be found that the tensile strength, porosity and liquid absorption of the battery separators prepared in Examples 5-6 are improved, which shows that the introduction of cellulose acetate in the present application can inhibit the crystallinity of polyvinylidene fluoride, increase the porosity of the polyvinylidene fluoride film, and improve the affinity between the polyvinylidene fluoride film and the electrolyte.

[0053] 4. By comparing Examples 5-7 with Example 1, it can be found that the tensile strength, porosity and liquid absorption of the battery separators prepared in Examples 5-7 are all improved, which shows that the amount of acetate fiber added is optimized in this application, and the appropriate amount of addition can increase the porosity and mechanical strength of the polyvinylidene fluoride surface. The appropriate amount of nano-silicon dioxide is conducive to the formation of pores in the polyvinylidene fluoride film, and can be evenly dispersed in the polyvinylidene fluoride film and evenly play a supporting role.

[0054] 5. By comparing Examples 8-9 with Example 1, it can be found that the tensile strength, porosity and liquid absorption of the battery separators prepared in Examples 8-9 are all improved, which shows that the PET fiber used in this application can stably play the role of supporting material in the polyvinylidene fluoride film, form a stable staggered structure in the polyvinylidene fluoride film, and stably improve the mechanical strength of the film. Sodium alginate has better viscosity, which is beneficial to improve the bonding strength between the polyvinylidene fluoride film and the composite fiber membrane.

[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A porous battery separator, characterized in that: The invention comprises a polyvinylidene fluoride film, a composite fiber film and a polyvinylidene fluoride film which are arranged in sequence, wherein the composite fiber film is a silicon dioxide / zirconia fiber film.

2. A porous battery separator according to claim 1, characterized in that: The composite fiber membrane is prepared as follows: polyvinyl pyrrolidone is added to HNO3, stirred to dissolve, and then N'N-dimethylformamide and vinyltrimethoxysilane are added in sequence and stirred to obtain solution A, zirconium n-butoxide and acetic acid are mixed to obtain solution B, a certain amount of solution B is added to solution A, and stirred to obtain a polyzirconium siloxane spinning solution, which is electrospinned to prepare a precursor fiber membrane, the precursor fiber membrane is dried at 80°C for 6 h, then placed in a muffle furnace, heated to 1000°C at a rate of 5°C / min in an air atmosphere, and kept warm for 1 h to obtain a composite fiber membrane.

3. A porous battery separator according to claim 2, characterized in that: The polyvinylidene fluoride film comprises polyvinylidene fluoride and silicon dioxide, and the silicon dioxide is amino silicon dioxide modified by a silane coupling agent.

4. A porous battery separator according to claim 3, characterized in that: The silicon dioxide is phosphoric acid-modified silicon dioxide.

5. A porous battery separator according to claim 4, characterized in that: The phosphorylated modified silica is prepared as follows: dispersing silica in water, adding phosphoric acid, stirring, volatilizing in a water bath, grinding, roasting, washing, and drying to obtain the phosphorylated modified silica.

6. A porous battery separator according to claim 4, characterized in that: The polyvinylidene fluoride film also includes cellulose acetate, and the mass ratio of the polyvinylidene fluoride to cellulose acetate is 8-9:1-2.

7. A porous battery separator according to claim 6, characterized in that: The mass ratio of polyvinylidene fluoride, cellulose acetate and nano-silicon dioxide in the polyvinylidene fluoride film is 8-9:1-2:0.

9.

8. A porous battery separator according to claim 6, characterized in that: PET fiber is added into the polyvinylidene fluoride.

9. A porous battery separator according to claim 9, characterized in that: The PET fiber is PET fiber modified by sodium alginate.

10. The method for preparing a porous battery separator according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of composite fiber membrane: lay the composite fiber membrane flat on a glass plate; S2, polyvinylidene fluoride solution preparation: dissolving polyvinylidene fluoride-hexafluoropropylene powder in 1-methyl-2-pyrrolidone solution, stirring to obtain a mixed solution, adding nano-scale silicon dioxide powder, stirring to obtain a uniform solution, and obtaining a polyvinylidene fluoride solution; S3. Preparation of porous battery separator: Use a scraper to uniformly coat the casting liquid on both sides of the fiber membrane at a uniform speed. The coating amount of the casting liquid is 0.1 ml / cm 2 The ceramic fiber coated with the casting solution is dried at 80°C to evaporate the NMP solvent, and then dried to obtain a porous battery separator.